The critical thinking dispositions of students around coffee plantation area in solving algebraic problems - Dian, Kurniati; Moh, Zayyadi (International Journal of Engineering and Technology, 2018)
The present study aimed at describing the dispositions of students around a coffee plantation in solving algebraic problems, especially those pertaining to fraction and comparison. Critical thinking disposition denotes the initial milestone to developing studentsâ€™ critical thinking skills. The study investigated four components of critical thinking dispositions, comprising of truth-seeking, open-mindedness, self-confidence, and inquisitiveness. The subjects under investigation were 45 students at the second grade of a junior high school situated around Garahan coffee plantation in Jember district, East Java, Indonesia. The study covered several phases, inter alia, (1) describing problems on Algebra to the students, (2) recording any activities of the research subjects when doing tasks given, (3) analyzing the studentsâ€™ answer sheets based on four components of critical thinking dispositions, (4) conducting method triangulation projected to confirm the preliminary findings on the students critical thinking dispositions, and (5) determining the studentsâ€™ critical thinking dispositions based on the results of direct observation, video recording, and interview. The study gained several findings related to the studentsâ€™ dispositions. First, the studentsâ€™ tendency in truth-seeking was characterized by their analysis on the problems given on themes regarding coffee. This prevented them from making mistakes as they checked some information, be it known or unknown, as the bases for problem solving. However, not every student was aware of what was unknown about the problem or what was required to solve the problem. Second, their tendency in open-mindedness was evinced by the fact that they were assured of their answer as they related it to their experience in planting coffee. Nevertheless, some students tended to ask their parent when they had to determine the amount of diameter comparison between two logs to be connected. Third, they tended to be confident in solving problems given as they had experienced the activities described in the problem when they assisted their parents in planting coffee, but still some students had yet to be sure of their answers as they lacked the experience in planting coffee. Lastly, they tended to possess sound inquisitiveness concerning various issues pertinent to solving algebraic problems, especially themed on coffee. They acquired the inquisitiveness by observing the actual activity in their environment. Nonetheless, their inquisitiveness could not be generalized to algebraic lessons at school.Â